2013
DOI: 10.1139/cjm-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic evaluation of the secondary metabolism of antistaphylococcal environmental bacterial isolates

Abstract: The increasing occurrence of drug-resistant Staphylococcus aureus is exacerbated with a declining rate of antibiotic discovery, particularly those with new mechanisms of action. The decline in antibiotic discovery from traditional sources, such as soil actinobacteria, necessitates examination of lesser studied microbes. Here, we present a strategy to select for organisms that may have a propensity to result in new antistaphylococcal agents by using S. aureus as a bait organism, and selecting organisms that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Chitinophaga, a genus belonging to phylum Bacteroidetes, is one of the biomarkers in F_3 (Additional file 1 : Date S1) and was first described by Sangkhobol and Skerman ( 1981 ) when including strains of filamentous, chitinolytic, and gliding bacteria that are transformed into spherical bodies during aging. Previously, studies showed that Chitinophaga was the only known isolated Bacteroidetes antibiotic producer (Wyatt et al 2013 ). Elansolid A was isolated as the first macrolide antibiotic from Chitinophaga sancti (Steinmetz et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chitinophaga, a genus belonging to phylum Bacteroidetes, is one of the biomarkers in F_3 (Additional file 1 : Date S1) and was first described by Sangkhobol and Skerman ( 1981 ) when including strains of filamentous, chitinolytic, and gliding bacteria that are transformed into spherical bodies during aging. Previously, studies showed that Chitinophaga was the only known isolated Bacteroidetes antibiotic producer (Wyatt et al 2013 ). Elansolid A was isolated as the first macrolide antibiotic from Chitinophaga sancti (Steinmetz et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…With special reference to plants, secondary metabolites are found to be healthy ingredients that work as antimicrobials or disease-controlling agents [4]. Owing to the potential of antimicrobials against pathogenic and spoilage microorganisms, these secondary metabolites gain much importance for the application in food products [18][19][20]. They contain the properties of antimicrobials and antioxidants at the same time and so are considered as a beter option for food preservation as compared to synthetic preservatives [21].…”
Section: Natural Antimicrobial Agentsmentioning
confidence: 99%
“…A second Variovorax isolate ( V. paradoxus P4B (ref. 32 )) was found to possess another distinct NRPS/PKS gene cluster, corresponding to a putative lipopeptide ( Fig. 2b , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%